Vitamin D Deficiency is Associated with Anemia, Cardiovascular Risk, and Lifestyle - Hawro D. Ismael; Goran Q. Othman; Azad H. Amin; Jabbar H. Odey; Badraddin U. Abdullah; Hashem H. Abdulla; Layla A. Kareem; Hataw J. Taher (Polytechnic Journal)
Traditionally, Vitamin D has been associated primarily with bone health, while further investigations revealed that a sufficient amount is important for many organ functions. Data of 314 individuals were obtained from Erbil governorate public and private hospitals from patients admitted to there for testing their level of Vitamin D and other tests according to their doctor’s prescription. The variable related to their lifestyle, metabolic syndrome, and hematology evaluations were obtained. The body mass index, number of sleeping hours, number of hours spent with electronic devices, serum lipid level anemia-related tests were measured. The results showed that serum 25(OH) Vitamin D levels in studied individuals were related to hyperlipidemia serum cholesterol measures. The level of Vitamin B12 and Iron status were lower in the Vitamin D deficiency (VDD) individuals. Mean platelet volume was higher in vitamin-deficient patients which induces the risk of cardiovascular (CV) diseases. This finding suggests the relation between VDD and metabolic syndrome, CV, and anemia-related measurement.